CAUSES OF ADULT BRONCHIECTASIS IN NON CYSTIC FIBROSIS IN PATIENTS PRESENTING IN A TERTIARY CARE HOSPITAL OF KPK - Dr Gullali; Dr Maryam Hussain; Dr Wahaj Ul Hassan; Dr Hafsa Waqar; Dr Saliha Wazir; Dr Mehroon Razzaq (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Non-cystic fibrosis bronchiectasis remains a significant public health concern, particularly in low and middle-income countries like Pakistan, where limited research has been conducted on its causes. The disease is characterized by chronic airway inflammation and recurrent infections, leading to a spectrum of clinical presentations and necessitating comprehensive etiological investigation.Objective: To identify the predominant causes of non-cystic fibrosis bronchiectasis among adults in a tertiary care hospital in Khyber Pakhtunkhwa (KPK), Pakistan.Methods: This prospective observational cohort study included 120 patients diagnosed with non-cystic fibrosis bronchiectasis based on clinical presentation and HRCT findings. Participants aged 20-80 years who provided written informed consent were included. The study excluded patients with ILD, traction bronchiectasis, cystic fibrosis, and those with a history of childhood onset bronchiectasis. Data were collected via structured questionnaires and analyzed using descriptive and inferential statistics.Results: The study revealed that infectious causes were the most prevalent, with tuberculosis (TB) accounting for 55% (n=66) of the cases, followed by pneumonia at 10% (n=12). COPD was identified in 15% (n=18) of the patients, ABPA in 7% (n=8), idiopathic causes in 8% (n=10), non-tuberculous mycobacteria (NTB) in 3% (n=4), and Kartagener syndrome in 2% (n=2). The mean age of participants was 51.99 years (SD=15.74), with a predominance of males (65%, n=78).Conclusion: The study highlights post-TB bronchiectasis as the leading cause of non-cystic fibrosis bronchiectasis in the adult population of KPK, underscoring the need for targeted interventions focusing on TB management and prevention.